Functional versus non-functional social support in a sample of chronic patients. Repercussion on health and treatment compliance - Martos Méndez, María José; Pozo Muñoz, Carmen (Anales de Psicología / Annals of Psychology, 2010)
In this paper we analyse both social functional and “non-functional” or problematic support, with regard to health, well-being and adherence to treatment. The sample of the present study consists of a total of 202 patients, of which 68% are female and 32% male. The results show a significant relation between the social support (functional and non-functional) they receive and their health and adherence to treatment. The best predictors in terms of their health are the social support from the patient ́s partner and from the medical staff, and the non-functional support from the latter. As far as the patients ́ well-being is concerned, the importance of medical social support is stressed once more, followed by that of their family and partner. As to the lack of adherence to treatment, the best predictors for this are global social support and non-functional support from friends. In short, although social functional support has a positive influence on the health and treatment adherence of the patients analysed, the negative impact that non-functional support behaviours can have on their well-being and treatment adherence is also important.